Effects of various levels of metabolizable energy in pre-starter diets of broiler chickens on growth performance - Sedgh-Gooyaa, Shadi; Mohebbifar, Ahmad; Torki, Mehran; Soleimanibaghshah, Loghman; Kamyab, Abdolreza (Journal of Poultry Sciences and Avian Diseases, 2024)
The pre-starter diet is critical for providing adequate nutrition to newly hatched chicks, whose digestive systems are not yet fully developed to handle solid feeds. Different levels of dietary energy can impact the growth and development of broilers. Hence, providing the right energy to meet their requirements is necessary. A study was conducted to examine the effect of different levels of metabolizable energy (ME) (3025, 2904, and 2783 kcal/kg) in the pre-starter diet (1 to 10 days) of broiler chickens on their growth performance traits. The experiment involved 450 broilers of the Ross 308 breed, divided into three treatments and six replications. The results of the study showed that reducing dietary energy levels increased the feed intake (FI) and body weight (BW) of broiler chickens, although it did not affect their feed conversion factor (FCR). Based on the results of the current study, reducing the recommended energy levels by up to 5% had no negative impact on growth performance. This can be useful in reducing the feed expense in broiler production.